2020
DOI: 10.3390/nu12041112
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Relationship between Type 2 Diabetes and Taste Function in Patients with Good Glycemic Control

Abstract: Type 2 diabetes mellitus (T2DM) has a very high impact on quality of life as it is characterized by disabling complications. There is little evidence about taste alterations in diabetes. Since many individual factors are involved in the onset of diabetes, the purpose of our study is to search a possible link between diabetes and individual taste function. Thirty-two participants with T2DM and 32 volunteers without T2DM (healthy controls) were recruited. Four concentrations of each of the four basic tastes (swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 27 publications
2
18
2
Order By: Relevance
“…In the euglycemia state, T1R2 expression in humans increased in both healthy and diabetic subjects after intraduodenal glucose infusion, whereas during hyperglycemia, lower T1R2 expression was observed in healthy controls, and in diabetics there were no variations (Young et al., 2009). More recently, one study performed in 2020 reported significant differences in the ability to recognize sweet taste between T2DM patients and healthy controls, independently of their sex, glycemic control, and time since diagnosis (Pugnaloni et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the euglycemia state, T1R2 expression in humans increased in both healthy and diabetic subjects after intraduodenal glucose infusion, whereas during hyperglycemia, lower T1R2 expression was observed in healthy controls, and in diabetics there were no variations (Young et al., 2009). More recently, one study performed in 2020 reported significant differences in the ability to recognize sweet taste between T2DM patients and healthy controls, independently of their sex, glycemic control, and time since diagnosis (Pugnaloni et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Food choices for a molecular dietary pattern developing an insulin-resistant metabolic state Compared to normal glycemic adults, adults with Type 2 Diabetes make different food choices, favoring a high saturated fat diet with higher total fat and protein and less fiber, as reported by Breen et al [50]. Increased insulin resistance favors continued unhealthy food choices via aberrant central insulin action, as reported by Tiedemann et al [51], leading to a vicious cycle in which insulin resistance drives changes in taste perception, as observed by Pugnaloni et al [52], leading to continued eating and snacking behavior. Saturated fat increases intramuscular triglycerides, and a decreased intake of saturated fatty acids could be beneficial in reducing intramuscular triglycerides and the associated risk of diabetes, according to data from Luukkonen et al [53].…”
Section: Bmi Is Not the Main Driver For Insulin Resistance; Insulin Resistance Drives Bmimentioning
confidence: 93%
“…A number of possible methods to prevent, attenuate or cure this side-effect have been recently reviewed [ 41 ]. Taste and smell alterations may also be caused by chemotherapy regimens, particularly in previous smokers, females or in head and neck cancer patients, and may contribute to malnutrition [ 42 , 43 ]. Apart from epithelial damages, chemotherapy-induces changes in the expression of specific genes that have been linked to dysgeusia and to mild/moderate stomatitis [ 44 ].…”
Section: Nutritional Care During Active Chemotherapy: Any New Tricks For This Old Issue?mentioning
confidence: 99%